ANALISIS STRUKTUR MELODI LAGU DUA MATA SAYA KARYA PAK KASUR - Fithri Meiliawati (UIN Sultan Maulana Hasanuddin Banten, 2021)
A song masterpiece by Pak Kasur entitled Dua Mata Saya, My two eyes, is very interesting to be reviewed deeply. It can be seen from the structure of the melody and the lyric that has educational meaning and value. The method that is used in this research is descriptive analysis by collecting all the data and then the data are classified, validated and interpreted. This research shows that the melody structure that is made has clear pattern, the lyric is simple and easy hence children are able to pronounce it and it is appropriate according to the characteristic of children’s song. Key Word: Analysis, Structure Melody, children songReferences Fitriyyah, D. (2016). Membangun Karakter Anak Melalui Dongeng. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 1(1), 1–10. Hartono. (1995). Pengetahuan Suara dan Musik. Interaksara. Hayati, N. R. (2016). Pendidikan Pra Sekolah (Pendidikan Anak Usia Dini) Dalam Islam. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 72–82. Huliyah, M. (2016a). Hakikat Pendidikan Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 60–71. Huliyah, M. (2016b). Pengembangan Daya Seni Pada Anak Usia Dini. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 1(2), 149–164. Hurlock, E. B. (2016). Perkembangan Anak (Vol. 2). Penerbit Erlangga. Kriswanto, Y. J. (2020). PERAN MUSIK SEBAGAI MEDIA INTERVENSI DALAM LINGKUP PRAKTIK KLINIS. IKONIK : Jurnal Seni dan Desain, 2(2), 81–86. https://doi.org/10.51804/ijsd.v2i2.737Kusumawati, I. (2016). Pengembangan Karakter Siswa Raudlatul Athfal Berbasis Pendidikan Agama Islam. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 1(2), 139–148. Mack, D. (1994). ilmu Melodi. Pusat Musik Liturgi. Mack, D. (1996). Teori Dasar Musik dan Harmoni Tonal. Pusat Musik Liturgi. Moeradi, H. (2009). Komposisi Musik dan Aransemen. Munawaroh, H., Imroatun, & Ibrohim, B. (2019). Upaya Peningkatan Rasa Percaya Diri Aud Melalui Kegiatan Bernyanyi Di Depan Kelas. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 4(2), 133–142. Prier, K.-E. (2004). Ilmu Bentuk Musik. Pusat Musik Liturgi. Raharjo, E. (2007). MUSIK SEBAGAI MEDIA TERAPI. Harmonia: Journal of Arts Research and Education, 8(3). Soeharto, M. (1986). Belajar Membuat Lagu. PT. Gramedia. Sudharsono, J. (1998). Ambitus. Pusat Musik Liturgi. Syukur, S. (2009). Harmoni 1, Prinsip-prinsip Dasar Pembelajaran Harmoni Tonal Bara. CV. Bintang Warli Artika.